The Implementation Of The First Pillar Of Responsibility To Protect In Indonesia: Critical Analysis Of Law On Social Conflict Management - Sefriani Sefriani (Fakultas Hukum Universitas Islam Indonesia, 2020)
Responsibility to Protect Principle (R2P) is intended to accomplish the humanitarian intervention principle which considered has a failure in many aspects. However, the existence of this principle still leaves worry, especially for a developing country, over manipulation and politics in its implementation. The formulated problems for this research are (1) how is the development of the R2P principle in International Law? (2) how is the implementation of the first pillar of R2P to prevent mass atrocities crime in the Indonesian government? The result shows that R2P gained more supports and was adopted in General Assembly resolution, completed with three pillars and six thresholds for its implementation. The implementation of the first pillar of R2P in Indonesia as a state responsibility to protect the society from mass atrocities crime has not been conducted properly. Although Indonesia already had a law on social conflict management, however, minimum law enforcement arrangement; high impunity culture, lack of knowledge about R2P, revocation of law on CTR, the impartiality of governmenttowards some majority groups potentially make the implementation of the first pillar of R2P in Indonesia will be failed.